Serum Cytokines in Young Pediatric Patients with Congenital Cardiac Shunts and Altered Pulmonary Hemodynamics - Leína Zorzanelli; Nair Yukie Maeda; Mariana Meira Clavé; Vera Demarchi Aiello; Marlene Rabinovitch; Antonio Augusto Lopes (Mediators of Inflammation)
Background and Objective. Inflammation is central in the pathogenesis of pulmonary hypertension. We investigated how serum cytokines correlate with clinical features, hemodynamics, and lung histology in young patients with pulmonary hypertension associated with congenital cardiac shunts. Design. Prospective, observational study. Methods and Results. Patients (n=44) were aged 2.6 to 37.6 months. Group I patients (n=31) were characterized by pulmonary congestion and higher pulmonary blood flow compared to group II (p=0.022), with no need for preoperative cardiac catheterization. Group II patients (n=13) had no congestive features. At catheterization, they had elevated pulmonary vascular resistance (5.7 [4.4–7.4] Wood units·m2, geometric mean with 95% CI). Cytokines were measured by chemiluminescence. Macrophage migration inhibitory factor (MIF) was found to be inversely related to pulmonary blood flow (r=-0.33, p=0.026) and was higher in group II (high pulmonary vascular resistance) compared to group I (high pulmonary blood flow) (p=0.017). In contrast, RANTES chemokine (regulated on activation, normal T cell expressed and secreted) was characteristically elevated in Group I (p=0.022). Interleukin 16 was also negatively related to pulmonary blood flow (rS=-0.33, p=0.029) and was higher in patients with obstructive vasculopathy at intraoperative lung biopsy (p=0.021). Conclusion. Cytokines seem to be important and differentially regulated in subpopulations of young patients with cardiac shunts.